Strategi Badan Pengawas Pemilihan Umum Dalam Mencegah Money Politic Di Kabupaten Sinjai (Studi Kasus Pilkada 2018) - Indasari, Indasari; Burhanuddin, Burhanuddin; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to describe how the general election supervisory body's strategy in preventing money politics in Sinjai district (2018 election case study). The method used  was case study. There were 9 informants, including the community. The results of this study showed that the strategy used to prevent money politics in Sinjai District by making efforts to improve both internally and externally to improve the performance of the Election Supervisory Body and see how the quality of the Election Supervisory Body itself. Bawaslu provided technical guidance and training to each personnel / committee involved in the election activities as supervisors in accordance with the methods used, as well as utilizing electronic media and internet media to conduct supervisory controls. The determinant factor so that the emergence of money politicians was with the desire to occupy an office instantly by relying on money as a bribe to ordinary people.